Advancing Pain Understanding and Drug Discovery: Insights from Preclinical Models and Recent Research Findings - Yahya I. Asiri; Sivakumar S. Moni; Mohankumar Ramar; Kumarappan Chidambaram (MDPI AG, 2024)
Despite major advancements in our understanding of its fundamental causes, pain-both acute and chronic-remains a serious health concern. Various preclinical investigations utilizing diverse animal, cellular, and alternative models are required and frequently demanded by regulatory approval bodies to bridge the gap between the lab and the clinic. Investigating naturally occurring painful disorders can speed up medication development at the preclinical and clinical levels by illuminating molecular pathways. A wide range of animal models related to pain have been developed to elucidate pathophysiological mechanisms and aid in identifying novel targets for treatment. Pain sometimes drugs fail clinically, causing high translational costs due to poor selection and the use of preclinical tools and reporting. To improve the study of pain in a clinical context, researchers have been creating innovative models over the past few decades that better represent pathological pain conditions. In this paper, we provide a summary of traditional animal models, including rodents, cellular models, human volunteers, and alternative models, as well as the specific characteristics of pain diseases they model. However, a more rigorous approach to preclinical research and cutting-edge analgesic technologies may be necessary to successfully create novel analgesics. The research highlights from this review emphasize new opportunities to develop research that includes animals and non-animals using proven methods pertinent to comprehending and treating human suffering. This review highlights the value of using a variety of modern pain models in animals before human trials. These models can help us understand the different mechanisms behind various pain types. This will ultimately lead to the development of more effective pain medications.